ANALYSIS OF LEGAL PROTECTION AGAINST VIOLENCE AGAINST CHILDREN IN INDONESIA: ANALISIS PERLINDUNGAN HUKUM TERHADAP TINDAK KEKERASAN PADA ANAK DI INDONESIA - Ndruru, Felianis (LPPM UPMI, 2023)
Violence against children in Indonesia from time to time continues to occur and increasingly various forms. In fact, children are the successors and assets owned by the nation that will maintain and realize the ideals of the nation. Pindakan is a behavior that violates the law and will be given sanctions to the perpetrators who do this. At present many crimes are often carried out such as violence. Violence is an arbitrary act carried out by someone with the aim of hurting physically and psychologically. Parents have an important role to maintain and protect but actually acts of violence against children are carried out by their closest people like parents. Then the need for a way so that acts of violence against children are not continuously carried out and must be given firm action by the government to the perpetrators who did this. This paper examines how legal protection efforts for children as victims of violence that occurred in Indonesia.